Factors Associated with Men’s Awareness of Danger Signs of Obstetric Complications and Its Effect on Men’s Involvement in Birth Preparedness Practice in Southern Ethiopia, 2014 - Alemu Tamiso Debiso; Behailu Merdekios Gello; Marelign Tilahun Malaju (Advances in Public Health)
Background. Compared to average maternal mortality ratio of 8 per 100,000 live births in industrialized countries, Ethiopia has an estimated maternal mortality ratio of 676 per 100,000 live births. Maternal deaths can be prevented partially through increasing awareness of danger signs of obstetric complications and involving husbands (male) in birth preparedness practice. Methods. Community based cross-sectional study was done. All adult males with a wife or partner who lives in the selected kebeles were our study population. Data was collected by pretested and structured questionnaires and two-stage cluster sampling procedure was used in order to collect study samples. Data was cleaned and entered into Epi Info 7 and exported to SPSS (IBM-21) for further analysis. Ordinary and hierarchical logistic regression model were used and AOR with 95% CI were used to show factors and the effect of men’s awareness of danger sign on men’s involvement in birth preparedness practice. Results. Total numbers of men interviewed were 836 making a response rate of 98.9%. 42% of men had awareness of danger sign and 9.4% (95% CI: (7.42, 11.4) of men were involved in birth preparedness practice. Respondents who live in the rural area [(AOR: 8.41; (95% CI: (4.99, 14.2)], governments employee [(AOR: 3.75; (95% CI: (1.38, 10.2)], those who belong to the highest wealth quintile [(AOR: 3.09; (95% CI: (1.51, 6.34)], and husbands whose wives gave birth in the hospital [(AOR: 2.09; (95% CI: (1.29, 3.37)], health center [(AOR: 1.99; (95% CI: (1.21, 3.28)], and health post [(AOR: 2.2; (95% CI: 2.16 (1.06, 404)] were positively associated and those who had no role in the health development army [(AOR: 0.43; (95% CI: (0.26, 0.72)] were negatively associated with men’s awareness of danger signs of obstetric complications. Conclusion. The prevalence of men awareness of danger sign was low and male involvement in birth preparedness practice was very low. Since there is a low level of awareness (17.1%) particularly in the urban area and men act as gatekeepers to women’s health, the respective organization needs to review urban health extension program and give due emphasis to husband education in order that they are able to recognize danger signs of obstetric complications in a way to increase their involvement in birth preparedness practice.